Electron heating by HF pumping of high-latitude ionospheric F-region plasma near magnetic zenith - Leyser, Thomas B; Gustavsson, Björn Johan; Rexer, Theresa; Rietveld, Michael T (Annales Geophysicae, 2020)
High-frequency electromagnetic pumping of ionospheric F-region plasma at high and mid latitudes gives the strongest plasma response in magnetic zenith, antiparallel to the geomagnetic field in the Northern Hemisphere. This has been observed in optical emissions from the pumped plasma turbulence, electron temperature enhancements, filamentary magnetic field-aligned plasma density irregularities, and in self-focusing of the pump beam in magnetic zenith. We present results of EISCAT (European Incoherent SCATter association) Heating-induced magnetic-zenith effects observed with the EISCAT UHF incoherent scatter radar. With heating transmitting a left-handed circularly polarized pump beam towards magnetic zenith, the UHF radar was scanned in elevation in steps of 1.0 and 1.5∘ around magnetic zenith. The electron energy equation was integrated to model the electron temperature and associated electron heating rate and optimized to fit the plasma parameter values measured with the radar. The experimental and modelling results are consistent with pump wave propagation in the L mode in magnetic zenith, rather than in the O mode.